Identification of Emergent Research Issues: the Case of Optoelectronic Devices - Roche, Ivana; Vedovotto, Nathalie; Besagni, Dominique; François, Claire; Mounet, Roger; Schiebel, Edgar; Hörlesberger, Marianne (IntechOpen, 2011)
None